Corrective Feedback and Learner Uptake in a Young Children Bilingual Classroom - W, Adesia Kusuma (Indonesian Journal of English Language Studies (IJELS), 2018)
Most research on corrective feedback and learner uptake inspired by Lyster and Ranta (1997) has been conducted with students belonging to various age groups. This study was undertaken to investigate the occurrence of corrective feedback and uptake in young children bilingual context whose age ranged from 5 to 6 or children in bilingual kindergarten in Indonesia. Transcripts of 100 minutes of lessons in Blossoms class of Satya Wacana Children Centre, Salatiga, were analyzed to answer these two research questions: (1) What types of learner errors lead to what types of corrective feedback in young children bilingual classroom? and (2) what is the uptake rate of each type of feedback and the relationship between learner errors, feedback, and learner uptake? The results revealed that the majority feedback provided for grammatical errors was repetition. The majority feedback given on phonological errors was recast. Then, explicit correction was the most frequent feedback for lexical errors. This study also found that elicitation and repetition led to the highest uptake rate. Although recast in this study did not lead to a high uptake rate compared with other types of feedback, in the case of phonological errors, recast did lead to a high uptake and repair rate. This study also provided an integrated picture about the relationship between learner errors, feedback, and learner uptake. Overall, there were differences in the patterns of feedback and uptake between this study and previous studies, which were interpreted with the reference to the unique characteristics of the instructional context.Â Keywords: Corrective feedback, uptake, bilingual young children